Synthetic MRI in the detection and quantitative evaluation of sacroiliac joint lesions in axial spondyloarthritis - Zhang, Ke; Liu, Chaoran; Zhu, Yunfei; Li, Wenjuan; Li, Ximeng; Zheng, Jing; Hong, Guobin (Frontiers in Immunology, 2022)
Objective: To test the hypothesis that synthetic magnetic resonance imaging (MRI) produces morphologic MR images with similar detection rates of sacroiliac joint lesions in axial spondyloarthritis (axSpA) patients than does conventional MRI. Further to assess quantitative value of quantitative mapping generated by synthetic MRI in bone marrow edema (BME) and fat metaplasia. Methods: A total of 132 axSpA patients underwent synthetic and conventional MRI from October 2019 to March 2021 were included in this prospective study. Two independent readers visually evaluated active inflammatory (BME, capsulitis, enthesitis, and Inflammation at site of erosion) and structural lesions (erosion, fat metaplasia, sclerosis, and ankylosis) of sacroiliac joints respectively on conventional and synthetic MR images. T1, T2, and proton density (PD) values generated by synthetic MRI quantitative mapping further quantitatively evaluate BME and fat metaplasia. A McNemar test was used to compare the difference between two methods in visual analysis of sacroiliac joint lesions. Intra-class correlation coefficient (ICC) was used to assess the inter-reader consistency of quantitative values. Mann-Whitney test, receiver operating characteristic (ROC) curve and area under the receiver (AUC) were performed for all quantitative analysis. Results: There were no statistical difference between conventional and synthetic MRI in visual analysis of sacroiliac joint lesions (all P＞0.05). 103 BME and 111 fat metaplasia were evaluated quantitatively by T1, T2, and PD values. Inter-reader consistency of quantitative values were all good (ICC, 0.903~0.970). T1 and T2 values of BME were all higher than those of the normal marrow (P＜0.001). However, There was no significant difference in PD value between BME and normal marrow (P=0.830). T2 and PD values of fat metaplasia were all higher than normal marrow, and T1 value of fat metaplasia was lower (P＜0.001). T1 value (AUC, 0.99) showed higher diagnostic efficacy of BME than T2 value (AUC, 0.78). T1 (AUC, 0.88), T2 (AUC, 0.88) and PD (AUC, 0.88) values were no significant difference in the diagnostic efficiency of fat metaplasia. Conclusion: Synthetic MRI could achieve similar detection rates of sacroiliac joint lesions in axSpA compared with conventional MRI. Furthermore, synthetic quantitative mapping could be used for accurately quantify BME and fat metaplasia.